Histological and histomorphometrical evaluation of furcation perforations filled with MTA, CPM and ZOE - da Silva, G. F. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Sasso-Cerri, E. [UNESP]; Tanomaru-Filho, M. [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley-Blackwell Publishing, Inc, 2011)
P>AimTo evaluate the biological response of the periodontium adjacent to furcation perforations in rat molars filled with Endo-CPM-Sealer (CPM), MTA-Angelus (MTA) or zinc oxide-eugenol cement (ZOE).MethodologyThe pulp chamber floors of maxillary right first molar teeth were perforated and sealed with CPM, mineral trioxide aggregate (MTA) or ZOE; the left first molars, without any treatment, were used as controls (CG). After 7, 15, 30 and 60 days, fragments of maxilla were fixed, decalcified and embedded in paraffin. Sections were stained with H&E, Masson's trichrome and submitted to tartrate-resistant acid phosphatase (TRAP) reaction, used as an osteoclast marker. The width of the periodontal space, the numerical density of inflammatory cells and the number of TRAP-positive osteoclasts in the bone surface were measured, and statistical analyses were performed using analysis of variance and Tukey test (P < 0.05).ResultsIn all experimental groups, the greatest number of inflammatory cells was observed at 7 days, especially in the ZOE group. In this group, the intense inflammatory process was related to a significant increase (P < 0.05) in the number of osteoclasts and, thereby, in an increase in the width of the periodontal space. At 60 days, no significant differences in osteoclast numbers amongst CPM, MTA and CG groups occurred; the periodontal space was also significantly reduced in the experimental groups in comparison with the initial periods. However, in the ZOE group, the periodontal space was significantly larger (P < 0.05) in comparison with MTA-based materials.ConclusionsThe periodontium adjacent to perforations filled with MTA and CPM exhibited clear evidence of re-establishment and thus better biocompatibility than ZOE.
Keywords: biocompatibility; furcal perforations; mineral trioxide aggregate